1996
DOI: 10.1152/ajpheart.1996.270.1.h151
|View full text |Cite
|
Sign up to set email alerts
|

Exercise- and hypertension-induced collagen changes are related to left ventricular function in rat hearts

Abstract: Chronic hypertension, known to affect the collagen profile of the heart, and exercise result in impaired or improved heart function, respectively. Collagen types I [alpha 1(I)2 and alpha 2(I)] and III [alpha 1(III)3] are the predominant interstitial collagens thought to influence cardiac function, and the ratio of type III to I (collagen III/I) is thought to be a significant factor in the altered relaxation observed in hypertrophy. The present study tested the hypothesis that the myocardial structure and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 0 publications
2
32
2
1
Order By: Relevance
“…Conversely, attenuation of end-diastolic stiness has been associated with a reduction in myocardial collagen content and cross-linking (Bing et al 1978;Kato et al 1995). With regard to exercise-induced alterations in cardiac diastolic function, only one study has investigated the potential contribution of alterations in the properties of myocardial collagen towards changes in LV diastolic performance (Burgess et al 1996). Contrary to our results, the latter authors concluded that a relationship exists between adaptations in LV collagen and changes in diastolic performance following an exercise training programme.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Conversely, attenuation of end-diastolic stiness has been associated with a reduction in myocardial collagen content and cross-linking (Bing et al 1978;Kato et al 1995). With regard to exercise-induced alterations in cardiac diastolic function, only one study has investigated the potential contribution of alterations in the properties of myocardial collagen towards changes in LV diastolic performance (Burgess et al 1996). Contrary to our results, the latter authors concluded that a relationship exists between adaptations in LV collagen and changes in diastolic performance following an exercise training programme.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the goal of the latter study was to examine the eects of physical stress on myocardial collagen. Hence, an intensive treadmill running regimen (3 h Á day À1 Y 7 days Á week À1 ), as opposed to a regular 1 h Á day À1 , 5 days Á week À1 programme, utilised by others (Burgess et al 1996;Thomas et al 1992) and by ourselves, was employed by Bartosova et al (1969). Our data con®rm the inability of moderate habitual exercise, commenced in young rats, to aect collagen concentrations in the LV.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Some authors have reported an increase in cardiac or left ventricular mass, or both, relative to body weight after physical training. 25,26 This has not been confirmed by others. 24 It has been suggested that this may be due to a substantial decrease in body weight with relatively little change in cardiac mass.…”
Section: Cardiovascular Fitnesscontrasting
confidence: 56%